Heparin-like activity in uterine fluid. Issue 6133 (29th July 1978) - Foley, M E; Griffin, B D; Zuzel, M; Aparicio, S R; Bradbury, K; Bird, C C; Clayton, J K; Jenkins, D M; Scott, J S; Rajah, S M; McNichol, G P
Abstract : Uterine fluid was collected from a group of normal patients and a group of patients with menorrhagia. Heparin-like activity was detected in 34 out of 38 samples using an anti-Xa heparin assay. The heparin-like activity in uterine fluid was inhibited by adding the heparin antagonist hexadimethrine bromide to the assay. Concentrations of fibrinogen-fibrin degradation products (FDPs) were measured in five samples of uterine fluid. FDPs in the concentration detected had no effect on the anti-Xa assay. Heparin-like activity was higher in the group with menorrhagia, although the differences were not significant. Heparin-like activity increased throughout the menstrual cycle and decreased during menstruation, suggesting a possible cyclical variation in activity. There was no correlation between mast cell numbers in the endometrium and myometrium and heparin-like activity in uterine fluid and no correlation between the numbers and the stage in the menstrual cycle. In a few patients with intrauterine contraceptive devices (IUCDs) heparin-like activity was increased.